An Analytical Assessment of Potential Factors Contributing to tests Performance Variability in HIV screening tests in the Central Blood Bank in the Northern Borders Region of Saudi Arabia - Alanazi, Bader Mudhhi E; Vijayan, Hemapriyaa; Ayakannu, Rathimalar (Journal of Cultural Analysis and Social Change, 2026)
Accurate and reliable HIV screening is essential for effective diagnosis, treatment, and prevention. Variability in test performance can lead to false-positive or false-negative results, impacting patient care and public health efforts. Identifying the factors contributing to this variability is crucial for ensuring high-quality diagnostic services. This study employs a quantitative descriptive methodology to evaluate HIV screening tests at the Central Blood Bank in Saudi Arabia’s Northern Borders Region. A structured questionnaire was administered to 30 laboratory technicians to assess pre-analytical, analytical, and post-analytical factors affecting test performance. Statistical analysis was conducted to determine key areas contributing to variability. Findings indicate that significant pre-analytical associations with standardized blood collection procedures (p < 0.05) and regular staff training (p < 0.05). Analytically associations with quality control measures, including corrective actions, were significantly linked to reliability (p < 0.05). Post-analytically, resolving inconsistencies and outcome verification showed significant relationships (p < 0.05), underscoring their critical role in ensuring accurate results. Variability in HIV screening performance arises from multiple factors across pre-analytical, analytical, and post-analytical stages. Strengthening quality control, ensuring staff competency, and implementing standardized laboratory protocols are essential for improving HIV testing accuracy. These findings contribute to the development of targeted interventions aimed at enhancing the reliability of HIV screening programs and reducing diagnostic inconsistencies.